KEY TO EFFECTIVE COMMUNICATION : UPAYA KOMUNIKASI KELUARGA HARSAM (HARMONIS DAN KEBERSAMAAN) - Tri Prasetijowati; Fierda Nurany; Bagus Ananda Kurniawan; Rendi Rafi Pramudya Putra (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
Understanding the characteristics of each family member can also be used to build effective communication efforts within the family. Despite the fact that we are members of the same family, we have different personalities; Consequently, to foster harmony and unity in the family, communication must use different strategies. The purpose of this research is to find out the efforts and factors that hinder effective family communication. The purpose of this study is effective communication in families who live happily together. This research is descriptive qualitative, or describes various data obtained from interviews and observations. However, this research data collection method includes observation, interviews, and documentation. The study revealed the following: Openness, empathy, support, positive feelings, and equality are characteristics of families that work well together in their communication efforts. This attitude produces family harmony. Trust, supportive attitude, and open attitude are supporting factors for communication. Psychological (emotional) barriers and lack of time are encountered when family members communicate to achieve family harmony. When communicating with family members who are motivated by various circumstances and circumstances, these two factors influence attitudes.